Guava root-knot nematode Meloidogyne enterolobii - Chang Liu; Zane J. Grabau; Johan Desaeger (EDIS, 2022)
Meloidogyne enterolobii is an emerging destructive pathogen. The aim of this manuscript is to help growers be aware of the symptom, distribution, destructiveness and management measures of this nematode.